Identification of proteins of Francisella tularensis induced during growth in macrophages and cloning of the gene encoding a prominently induced 23-kilodalton protein. - Golovliov, I (1997)
The adaptation of facultative intracellular bacteria to host macrophages involves regulation of the synthesis of bacterial proteins. We analyzed the protein synthesis of Francisella tularensis LVS growing intracellularly in the macrophage-like murine cell line J774 and extracellularly in culture medium. After pulse-labeling with [35S] methionine and separation by one- and two-dimensional polyacrylamide gel electrophoresis, induction of a few proteins during intracellular growth was demonstrated. One of them, a 23-kDa protein, was prominently induced in the macrophages and also when extracellularly growing F. tularensis was exposed to hydrogen peroxide. After isolation of the 23-kDa protein from a preparative two-dimensional gel, a 22-amino-acid N-terminal peptide and two peptides obtained by trypsin digestion were sequenced. Based on the sequences, degenerate oligonucleotides were constructed for use as primers in a PCR. Hybridization of amplified DNA to XbaI-digested LVS DNA identified the gene of the 23-kDa protein in a 1.3-kb DNA fragment. Nucleotide sequence analysis revealed an open reading frame encoding a putative protein of a calculated molecular mass of 22.2 kDa. The open reading frame was preceded by a sequence typical of ribosome-binding sites in Escherichia coli. The amplified gene was successfully expressed by the pTrc99A vector in E. coli under control of the trc promoter. The gene product showed the same mobility and immunoreactivity as the 23-kDa protein of F. tularensis. The deduced amino acid sequence showed no significant homology with protein sequences in current data banks. Thus, intracellular growth of F. tularensis in macrophages was associated with prominent upregulation of a novel 23-kDa protein.